O potrzebie kształcenia umiejętności tworzenia związków międzytekstowych na etapie nauczania akademickiego - Jochimczyk, Magdalena (Studia Edukacyjne, 2021)
The article aims to indicate the need to train the skill to make intertextual relationships. The article focuses in particular on the academic teaching level, as the ability to operate someone else’s word is its vital element. The publication proves that the need to train this skill stems from a number of reasons: the need to meet the requirements for academic texts, the high didactic value of incorporating source texts into the written production process and the unsatisfactory level of students’ ability to create intertextual relationships.